Education on the Making of Milkfist Crackers in Kencak Village (Bancaran), Bancaran District, Bangkalan, East Java - Riza Aulia Widyaningsih; Siti Rodiyah; Teguh Setiawan Wibowo (Jurnal Pengabdian Masyarakat Bestari, 2023)
Bandeng fish is a fish that is rich in vitamins and proteins, especially in the region of eastern Java and its surroundings. Fish Bandeng is even available every day in markets and supermarkets so that for the business of fish Bandeng, it can be processed for some purposes of the devotion of society. Fish Bandeng is processed as weed so that it can build an IKM in the village (Kencat) Bancaran Madura. By learning to make a process of weed bandeng fish, it can be meaded into a sales power that is beneficial for the village masyarakat (Kencat) Bancaran Madura.